INDIVIDUAL-INTEGRAL ASSESSMENT OF PREPAREDNESS AND POTENTIAL CAPABILITIES OF A SPORTS RESERVE IN NORDIC COMBINED - Zebzeev, V.V.; Zdanovich, O.S.; Maltsev, G.S.; Ivanov, D.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to to develop a methodology for individual-integral assessment of readiness and determination of the potential capabilities of a sports reserve in Nordic combined. Results and conclusions. The developed methodology for individual-integral assessment of preparedness and determination of the potential capabilities of a sports reserve in Nordic Combined consists of a number of key procedural and substantive components: organization of systemic pedagogical control over the preparedness of athletes; creation of a formula for calculating the individual-integral assessment of readiness and determining the potential capabilities of combined athletes; determination of the influence of each type of preparedness of the biathletes; inclusion in the formula of additional variables with the appropriate coefficients; development of a formalized table to determine the level of individual-integral assessment of preparedness and potential capabilities of Nordic athletes; determining the evaluation criteria for each type of preparedness and the final coefficient of the potential capabilities of Nordic skiers.